1989
DOI: 10.1111/j.1574-6968.1989.tb03124.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of low level trimethoprim resistance in faecal isolates obtained from apparently healthy Nigerian students

Abstract: Twenty‐four of 63 enteric Gram‐negative organisms (38.1%) which were isolated from 35 apparently healthy Nigerian students were found to have low trimethoprim resistance (MIC < 1000 mg/1). These isolates were also found to be resistant to several other antibiotics and trimothoprim resistance was found to be transferable from 15 (62.5%) of the trimethoprim resistant organisms into E. coli EC 1005. It is likely that the high percentage of trimethoprim resistance encountered in this study is related to the high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The extracts of the two most active plants M. tomentosa and T. heudelotti were further fractionated to ascertain the properties of the active ingredients. These were tested against 50 multidrug resistant isolates from clinical and environmental sources including the organisms from the family Enterobacteriaceae which are commonly involved in clinical infections and are known to be highly versatile at acquiring resistance characteristics (Lamikanra et al, 1989). Two versatile pathogens, P. aeruginosa, a major nosocomial pathogen with low intrinsic susceptibility to antimicrobial agents and very high ability to acquire resistance, and S. aureus were also among those tested The organisms studied covered gram positive and gram-negative isolates (Table 3) and the demonstrated activities of the fractions showed that these plants have a wide spectrum of activity.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of the two most active plants M. tomentosa and T. heudelotti were further fractionated to ascertain the properties of the active ingredients. These were tested against 50 multidrug resistant isolates from clinical and environmental sources including the organisms from the family Enterobacteriaceae which are commonly involved in clinical infections and are known to be highly versatile at acquiring resistance characteristics (Lamikanra et al, 1989). Two versatile pathogens, P. aeruginosa, a major nosocomial pathogen with low intrinsic susceptibility to antimicrobial agents and very high ability to acquire resistance, and S. aureus were also among those tested The organisms studied covered gram positive and gram-negative isolates (Table 3) and the demonstrated activities of the fractions showed that these plants have a wide spectrum of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Residents of developing countries often carry antibiotic-resistant fecal commensal organisms (13,88). Visitors to developing countries passively acquire antibiotic-resistant gut Escherichia coli, even if they are not taking prophylactic antibiotics, which suggests that they encounter a reservoir of antibiotic-resistant strains during travel (89).…”
Section: Dissemination Of Resistant Organismsmentioning
confidence: 99%
“…Prevalence of antibiotic resistance in commensal E. coli isolated from human sources in community settings in low-and middle-income countries. ,28,29,43,44,46,47,49,50,53,55,[58][59][60][61][62][63][64][65][66][68][69][70][71][72] …”
mentioning
confidence: 99%